Child protection and the care continuum : theoretical, empirical and practice insights - Fernandez, Elizabeth, 1942-; Delfabbro, Paul H. (Paul Howard) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This important new book critically examines the complex policy and practice issues surrounding child protection, including the impact of theoretical orientations, contemporary debates, policy initiatives and research findings, and maintains an emphasis on the ethics and values underpinning child welfare interventions. The book introduces policies that are central to understanding the position and needs of children and young people, and how policy and practice have been influenced by developments including the children's rights agenda. It also explores the most significant issue in child welfare. These include: the experience of maltreatment by children, the systems of child protection to safeguard them, the methods and challenges of risk assessment, and the wide range of policy and therapeutic interventions to respond to children's needs. The book also examines family support to promote children's wellbeing before considering provision for children and young people who are looked after in out of home care. There is also a final section that focuses on best practice in communicating and working with children and young people drawing on participatory, rights-oriented and resilience-based approaches, and supporting foster and adoptive carers and biological parents. Contributing in a substantive and clear manner to a growing international conversation about the present function and future directions for child welfare in contemporary societies, this textbook will be of interest to undergraduate and postgraduate social work students and those from allied disciplines, and professionals who are engaged in child welfare services"--
OCLC-licensed vendor bibliographic record.
Keywords: Child welfare; Children -- Social conditions; Children -- Services for; SOCIAL SCIENCE / Social Work